Sticks and carrots: managing groundwater overabstraction in La Mancha, Spain - Closas, Alvar; Molle, Francois; Hernández Mora, N. (International Water Management Institute, 2017)
This paper presents a historical analysis of the different policy tools used to manage and regulate groundwater abstraction in the Western Mancha aquifer. Without much initial regulation and control, groundwater resources and aquifer levels decreased dramatically, threatening agriculture and also highly valuable groundwater-dependent wetland ecosystems. The interplay between sticks and carrots used in La Mancha shows the necessity for regulatory bodies to complement soft management approaches based on incentives with the threat of sanctions and limitations. However, as this case study shows, each policy modality has its legal, administrative and practical loopholes, which can be negotiated and exploited by groundwater users to their own advantage. The paper also studies the distribution of decision-making power and how local dynamics and individual behaviors are linked to higher level policies and their impacts on groundwater management, with an emphasis on the effectiveness and limitations of these tools.